GE_GERICHTE P/19066/2015 vom 15. November 2016 - GE Cour de justice (2016)
VOL(DROIT PÉNAL); DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL); VIOLATION DE DOMICILE; BRIGANDAGE; CONTRAINTE SEXUELLE; TENTATIVE(DROIT PÉNAL); CONCOURS D'INFRACTIONS | CP.189; CP.22; CP.47; CP.49